2018
DOI: 10.1021/acs.organomet.8b00026
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyl Graphene as a Superior Support for Bulky Ruthenium-Based Olefin Metathesis Catalyst

Abstract: A Hoveyda-type catalyst decorated with two quaternary ammonium tags was synthesized and noncovalently grafted on SiO2, SBA-15, and on carboxyl graphene. A comparative study showed that the efficiency of the dual-anchored heterogeneous catalysts was highly dependent on the properties of the supporting material with graphene outperforming silicate supports. The graphene-immobilized complex exhibited excellent efficiency reflected in turnover numbers obtained in ring-closing metathesis and in self-metathesis of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…The control results of pore volumes shown that matrices prepared with TEOS had higher pore volumes than those prepared with TMOS, and exhibit better activity, Figures S4 and 3, respectively. Our results are in agreement with those of previous reports on the binding of these catalysts to other solid supports 34 , 37 . Pastva et al 34 and Kaczanowska et al 37 reported that heterogeneous catalyst activity tended to increase with the increase in the pore size of the support used for catalyst entrapment.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…The control results of pore volumes shown that matrices prepared with TEOS had higher pore volumes than those prepared with TMOS, and exhibit better activity, Figures S4 and 3, respectively. Our results are in agreement with those of previous reports on the binding of these catalysts to other solid supports 34 , 37 . Pastva et al 34 and Kaczanowska et al 37 reported that heterogeneous catalyst activity tended to increase with the increase in the pore size of the support used for catalyst entrapment.…”
Section: Resultssupporting
confidence: 94%
“…1 , A-C catalysts. We expected the quaternary ammonium group in the type 2 catalysts to strongly (but not covalently) bind to the silica surface by adsorption, probably via electrostatic bonds with the silanol groups and/or the oxides on the surface of the sol–gel matrix 34 , 35 , 37 , 67 . This bond should decrease catalyst leakage, even during a metathesis reaction conducted in a polar solvent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially in hybrid catalysts prepared by immobilization of well-defined Mo and Ru carbenes, these properties have proved particularly useful. Although some Ru carbenes have also been immobilized on other materials such as Metal-Organic Framework MOF [84], graphene [85,86], glass, wool, and paper [87], the data reported so far show that SBA-15 is the most promising support for effective, stable, and widely applicable catalysts.…”
Section: Discussionmentioning
confidence: 99%